2012
DOI: 10.1021/om300232h
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of N–CN and O–CN Bond Cleavage by an Iron Silyl Complex

Abstract: Using hybrid density functional theory calculations with the B3LYP functional, the reaction mechanisms for cleavage of R 2 N−CN (R  H, Me) and MeO−CN bonds in the presence of an unsaturated iron(II) silyl complex, CpFe(CO)SiMe 3 , were studied. The following sequence of reactions was shown to be favorable: (i) coordination of a nitrile through the lone pair of electrons on the nitrile N atom (N CN ) to form an end-on complex, (ii) isomerization of the endon complex to a side-on complex, (iii) migration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 122 publications
2
25
1
Order By: Relevance
“…[5] Most recently, Ni(0) and Pd(0) mediated C-CN bonds cleavage were reported. Related O-CN bond activations [6] have been realized in only a few cases while N-CN bond activation [7] is even rarer. Considering the paramount role of the elements such as nitrogen, oxygen and carbon in organic chemistry, moreover, the broad existence of cyano groups in natural ( e.g ., Cyanocycline A, Dnacin A1, Halimedin, Lahadinines A, et al) and/ or medical molecules ( e.g .,PPARgamma-active triterpenoid, 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid), along with the versatile application of cyano group towards spectacular precursor to vast functionalized groups, viz ., (i) amine; (ii) amide; (iii) acid; (iv) aldehyde; (v) ester; (vi) ketone; (vii) thioamide; (viii) hydroxyimidamide et al, reactions involved with such transformation can be of high importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Most recently, Ni(0) and Pd(0) mediated C-CN bonds cleavage were reported. Related O-CN bond activations [6] have been realized in only a few cases while N-CN bond activation [7] is even rarer. Considering the paramount role of the elements such as nitrogen, oxygen and carbon in organic chemistry, moreover, the broad existence of cyano groups in natural ( e.g ., Cyanocycline A, Dnacin A1, Halimedin, Lahadinines A, et al) and/ or medical molecules ( e.g .,PPARgamma-active triterpenoid, 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid), along with the versatile application of cyano group towards spectacular precursor to vast functionalized groups, viz ., (i) amine; (ii) amide; (iii) acid; (iv) aldehyde; (v) ester; (vi) ketone; (vii) thioamide; (viii) hydroxyimidamide et al, reactions involved with such transformation can be of high importance.…”
mentioning
confidence: 99%
“…Although other element-cyano bond cleavages, such as silyl-cyano, [12] germyl-cyano, [13] stannyl-cyano, [14] boryl-cyano, [15] sulfur-cyano, [16] and bromo-cyano [ 17 ] have been achieved, a useful synthetic transformation of oxy-cyano has not been reported yet. [6] In 2012, Nakao and co-workers disclosed palladium and triphenylborane catalyzed the intramolecular. oxycyanation of alkenes via the cleavage of O-CN bonds and the subsequent insertion of double bonds.…”
mentioning
confidence: 99%
“…Other element-cyano bond cleavages, such as silyl-cyano (1417), germyl-cyano (47,48), stannyl-cyano (4952), boryl-cyano (3946), sulfur-cyano (5356), and halo-cyano (57,58) have also been achieved, a useful synthetic transformation of oxy-cyano has not been reported until recently (59). …”
Section: Element-cn Bonds Activation Reactionsmentioning
confidence: 99%
“…In 2012, Nakao et al reported a reaction of the palladium and triphenylborane catalyzed the intramolecular oxy-cyanation of alkenes via the cleavage of O-CN bonds and the subsequent insertion of double bonds (Scheme 47) (59a). The reaction illustrated the cyano-fuctionalization of a double bond through cleavage of an oxygen-cyano bond, which is rare.…”
Section: Element-cn Bonds Activation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation